Molecular cloning, expression and enzymatic characterization of cytosolic glutathione stransferase from Acidovorax sp. KKS102 / Dayyabu Shehu - Dayyabu , Shehu (2018)
Glutathione S-transferases (GSTs) are a family of enzymes that function in the detoxification of a variety of electrophilic substrates. In this study, cloning and biochemical characterization of GSTs from Acidovorax sp. KKS102 were carried out. Database suggests that there are eleven putative GSTs in Acidovorax sp. KKS102. Phylogenetic analysis showed that the GSTs were distributed into Beta, Nu, zeta, Chi, while some did not show any particular class. Two GSTs (KKSG6 and KKSG9) were selected for further study. Sequence alignment showed that KKSG6 is closely related to BphK, a GST found within the operon responsible for PCB biodegradation in some organisms and showed dechlorination function against metabolites of polychlorobiphenyl degradation. The substrate specificity of KKSG6 included reacting with CDNB, ethacrynic acid, hydrogen peroxide and cumene hydroperoxide. Molecular docking, sequence alignment, and site-directed mutagenesis studies revealed some key amino acids that were found to play a crucial role in the catalytic activity of the protein. The C10F and A180P mutants displayed an increase in catalytic activity of the enzyme against CDNB and ethacrynic, however, the peroxidase activities did not show any significant change. In contrast, the K107T mutant displayed variable results toward various substrates suggesting its possible role in determining substrate specificity in this enzyme. Analysis of kinetic parameters using CDNB and GSH as substrates showed a high Km value of the enzyme for CDNB when compared to GSH. C10F and A180P mutants also displayed a decrease in the affinity of both CDNB and GSH to KKSG6 with a corresponding increase in Vmax and kcat, however, K107T showed decrease in Vmax and kcat. The enzyme also displayed dechlorination function against 2, 3, and 4-chlorobenzoates and 2,4- dichlorobenzoate. The C10F and A180P mutants both showed an increase in dechlorination function while K107T showed a variable result. The same trend of dechlorination activity was observed against DDT, endosulfan, and permethrin. Phylogenetic analysis revealed that KKSG9 is closely related to zeta class, however, it has possessed low sequence similarity to known zeta class GSTs. Functional analysis showed that the enzyme exhibits wider substrate specificity compared to most zeta class GSTs by reacting with 1-chloro-2,4-dinitrobenzene (CDNB), p-nitrobenzyl chloride (NBC), ethacrynic acid (EA), hydrogen peroxide, and cumene hydroperoxide. The enzyme also displayed dehalogenation function against dichloroacetate in addition to permethrin, and dieldrin. The mutant (Y12C) displayed low catalytic activity and dehalogenation function against all the substrates when compared with the wild type. Kinetic analysis using NBC and GSH as substrates showed that the mutant (Y12C) displayed a higher affinity for NBC when compared with the wild type, however, no significant change in GSH affinity was observed. The presence of a tyrosine residue in KKSG9 motif instead of commonly known Cys, Thr, Ser or Ala might represent an evolutionary trend toward improving the catalytic activity of the enzyme. These enzymes could be useful in the bioremediation of various classes of organochlorine pollutants.